The Association between Maternal Height, Body Mass Index, and Perinatal Outcomes - Marshall, Nicole E.; Biel, Frances M.; Boone-Heinonen, Janne; Dukhovny, Dmitry; Caughey, Aaron B.; Snowden, Jonathan M. (American Journal of Perinatology, 2019)
Objective To test the hypothesis that maternal height is associated with adverse perinatal outcomes, controlling for and stratified by maternal body mass index (BMI).Study Design This was a retrospective cohort study of all births in California between 2007 and 2010 (n = 1,775,984). Maternal height was categorized into quintiles, with lowest quintile (≤20%) representing shorter stature and the uppermost quintile (≥80%) representing taller stature. Outcomes included gestational diabetes mellitus (GDM), preeclampsia, cesarean, preterm birth (PTB), macrosomia, and low birth weight (LBW). We calculated height/outcome associations among BMI categories, and BMI/outcome associations among height categories, using various multivariable logistic regression models.Results Taller women were less likely to have GDM, nulliparous cesarean, PTB, and LBW; these associations were similar across maternal BMI categories and persisted after multivariable adjustment. In contrast, when stratified by maternal height, the associations between maternal BMI and birth outcomes varied by specific outcomes, for example, the association between morbid obesity (compared with normal or overweight) and the risk of GDM was weaker among shorter women (adjusted odds ratio [aOR], 95% confidence interval [CI]: 3.48, 3.28–3.69) than taller women (aOR, 95% CI: 4.42, 4.19–4.66).Conclusion Maternal height is strongly associated with altered perinatal risk even after accounting for variations in complications by BMI.
Keywords: cesarean; gestational diabetes; maternal height; obesity